2021
DOI: 10.1002/saj2.20240
|View full text |Cite
|
Sign up to set email alerts
|

Soil structure recovery following compaction: Short‐term evolution of soil physical properties in a loamy soil

Abstract: Soil compaction by farm machinery may persist for decades, hampering soil productivity and functioning. Assessing compaction costs and guiding recovery strategies are hindered by paucity of data on soil structure recovery rates. A long-term Soil Structure Observatory was established on a loamy soil in Switzerland to monitor soil structure recovery after prescribed compaction, and to better assess the roles of natural processes (vegetation, macrofauna, and shrink-swell cycles) on recovery patterns. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…In two previous meta‐analysis studies, a negligible effect of cover crops on bulk density was also reported (Alvarez et al., 2017; Blanco‐Canqui & Ruis, 2020). The change in bulk density usually results from vertical movement of soil particles (Keller et al., 2021). The cover crop roots only exert radial pressure on the surrounding soil and result in compression of the soil at approximately 1 mm around the roots (Angers & Caron, 1998; Koebernick et al., 2019), which does not necessarily induce vertical movement of soil particles and subsequent changes in bulk density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two previous meta‐analysis studies, a negligible effect of cover crops on bulk density was also reported (Alvarez et al., 2017; Blanco‐Canqui & Ruis, 2020). The change in bulk density usually results from vertical movement of soil particles (Keller et al., 2021). The cover crop roots only exert radial pressure on the surrounding soil and result in compression of the soil at approximately 1 mm around the roots (Angers & Caron, 1998; Koebernick et al., 2019), which does not necessarily induce vertical movement of soil particles and subsequent changes in bulk density.…”
Section: Discussionmentioning
confidence: 99%
“…Keller et al. (2021) suggested that air permeability and saturated hydraulic conductivity in compacted soil can be quickly improved, because they are determined by highly continuous biopores that can be easily formed by the roots of cover crops (Zhang et al., 2019). In this study, the strong taproots of the cover crops were able to create new continuous biopores or unblock the existing biopores, consequently enhancing the K s and K a60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we modelled and analyzed the subsoil compaction risk at a soil depth of 40 cm. Since this depth will not be reached by regular primary tillage and related loosening effects, soil compaction persists (Keller et al, 2017;Keller et al, 2021) and may not recover in short-term.…”
Section: Modelling Model Structure and Input Datamentioning
confidence: 99%
“…Overall, analyses of the spatio-temporal dynamics revealed that 1 year with increased precipitation can considerably affect the soil risk. This is particularly problematic as soil compaction, especially subsoil compaction, can be persistent for many years (Etana et al, 2013;Keller et al, 2017;Keller et al, 2021;Seehusen et al, 2021). Thus, 1 year of increased soil compaction risk accompanied by unsuited field traffic activities can be sufficient to affect soil functions and soil health in the long term.…”
Section: Spatio-temporal Variation Of Soil Compaction Riskmentioning
confidence: 99%